Analysis of wild honey development policy for local people livelihoods improvement in the Sumbawa District - Marcellinus M.B. Utomo; A.G.P Levina (Jurnal Penelitian Kehutanan Wallacea, 2018)
It has been more than five years Sumbawa becomes the center of wild honey development by Ministry of Environment and Forestry. However, scientific information of its condition is still lacking. This article aims to fill that gap and to discuss the efforts needed in order to make Sumbawan honey more contributes for local people in Sumbawa District. This paper assesses the effectiveness of the Ministry of Environment and Forestry’s supporting programs for wild honey development in The Sumbawa District using two indicators: livelihood capital development and problems on the ground accomplished. The results indicate the programs have not yet optimally developed local peoples’ livelihood capitals and many problems remain occurred on Sumbawan honey business development. This study suggests that works in these areas should be undertaken simultaneously, and encompasses strengthening contract agreement, both horizontally and vertically, and modifying the direction of current programs.